A STUDY TO ASSESS THE ATTITUDE OF MEDICAL STUDENTS TOWARDS LEARNING COMMUNICATION SKILLS IN A TEACHING HOSPITAL IN ANDHRA PRADESH - LATHA, R. ASHA; FARHANA, M. A.; SONIA, S. SHARON; RIYAZ, N. M.; MALLIKA, B. S. B (International Journal of Current Pharmaceutical Research, 2024)
Objective: Communication plays an essential role in present era of medical and health system where doctor should maintain good interpersonal relationship with patients. Teaching of communication skills to medical students as a part of the curriculum has gained importance in recent past. This study was conducted to assess attitude of medical students towards learning communication skills. Methods: Prior institutional ethical committee approval and prior informed consent obtained from participants. Study conducted among medical students of second and third year MBBS. Students were given a questionnaire (google forms). Questionnaire consisted of 26 items related to positive and negative attitude; 13 items in each subscale. Responses received were entered and analysed in Microsoft excel. Results: Total of 300 students participated, with a response rate of 76%. 132(57.9%) students were second year and 96(42.1%) were third year. 159(69.7%) students were females and 69(30.3%) were males. Reliability of scale was calculated using Cronbach’s Alpha, 0.859 for PAS and 0.704 for NAS; which were good and acceptable values. Better positive attitude scores (52.34±6.03) observed over negative attitude scores (40.07±6.40), implies students having a positive attitude towards learning communication skills. There were no significant differences between scores when compared between males and females and between second and third year MBBS students. Conclusion: Results of study emphasize that introduction of AETCOM learning modules in the medical curriculum has a positive impact on students towards learning communication skills. Doctor-patient inter-relationship, treatment decision-making, etc., are dependent on doctor’s communication skills; which can be improved and strengthened with AETCOM implementation in medical curriculum.